Neoadjuvant chemoradiation in older Irish adult patients with oesophageal cancer: a retrospective institutional review of clinical outcomes and hematological toxicity - Ronan Andrew McLaughlin; David McMahon; Christopher Cluxton; Orla Meave Fitzpatrick; Michael Conroy; Majid Almeraikhi; Humaid Alkaabi; Fianait Bligh; Brian O’Neill; Mayilone Arumugasamy; William Robb; Oscar Seamus Breathnach; et al. (BMC Cancer)
Abstract Background and objectives Neoadjuvant chemo-radiotherapy improves survival compared with surgery alone in locally advanced oesophageal cancer. In the Chemo-Radiotherapy for Oesophageal cancer followed by Surgery Study (CROSS) randomised controlled trial (RCT), the median age was 60. However, one third of patients diagnosed with oesophageal cancer are aged ≥ 70 years. The reported outcomes and toxicities from the CROSS RCT are therefore limited in their application to older adult patients. The proportion of older patients with oesophageal cancer is increasing globally due to prolonged life expectancy and an aging population. The aim of this study was to investigate the clinical outcomes and toxicity reported in older patients (≥ 70 years) treated with neoadjuvant chemo-radiation for oesophageal cancer compared with those aged < 70 years in a tertiary Irish cancer centre. Methods A retrospective cohort of patients treated with neoadjuvant chemo-radiation for oesophageal cancer was identified between 1st January 2015 and 1st January 2021. Eligible patients with cT1-4aNxM0 oesophageal cancer were identified in the Beaumont RCSI Cancer Centre database. Baseline characteristics and haematological toxicities were reported. Pathological response was reported. Chemotherapy toxicity was reported using the CTCAE Version 5.0. Survival was estimated using the Kaplan-Meier method. Survival between groups was compared using the log-rank test, and the Cox proportional hazards model was used to identify factors associated with overall survival (OS). Results In total 105 patients with potentially curable oesophageal cancer were included. One third (n = 35) of patients were ≥ 70 years (older cohort) and 70 (67%) aged < 70 years (younger cohort). In the older cohort, the median age was 75 (range: 70–86) and the younger cohort median age was 60 (29–69). The majority in both cohorts were male (73%). In 5 (14%) of the older and 7 (10%) younger cohort, individuals experienced ≥ grade 3 neutropoenia. In total, 80% of the older and 86% of the younger cohort proceeded to surgery. There was no difference in OS between the cohorts. There was also no difference in disease free survival (DFS) between the cohorts. Conclusion In conclusion, in patients aged ≥ 70 years compared to those aged < 70 years, we confirm that neoadjuvant chemoradiation is tolerable. There was no evidence to suggest any differences in OS and DFS between the cohorts. Neoadjuvant therapy in appropriately selected patients aged ≥ 70 years with oesophageal cancer is a reasonable treatment choice.